Growth of two lactic acid bacteria strains and their potential probiotic characteristics - YANG Jing; MA Ruhui; YANG Zhixi; XU Shuang; LI Duo; CHEN Lanming (浙江大学学报. 农业与生命科学版)
Probiotics are defined as “living micro-organisms which, upon ingestion in certain numbers, exert health benefits beyond inherent basic nutrition”. Recent reports have confirmed that probiotics can provide a variety of beneficial health effects, which are strain dependent. The regulation effect of probiotics was based on tolerance of acid environment in the stomach, and resistance to bile salt and trypsin in the small intestine. Most of lactic acid bacteria (LAB) are considered as probiotics, and have been widely used as dietary additives in cultured dairy foods and other fermentation products. The source of LAB may be naturally fermented food or human and animal intestines.In this study, two strains were isolated from Chinese traditional food (Northeast pickle and stinky beans), and identified as Lactobacillus plantarum D28 and Enterococcus faecium B21 by 16S rRNA gene sequences, respectively. The growth and potential probiotic characteristics of the two lactic acid bacteria strains were further investigated.Growth curve and the effect of initial pH on the growth were studied by spectrophotometry method. Meanwhile, the resistance characteristics were investigated, including sodium chloride (NaCl), bile salt, artificial gastric juice and artificial intestinal juice. In addition, antioxidant activity and bile salt hydrolase activity (BSH) in vitro were determined by scavenging DPPH (2, 2-diphenyl-1-picrylhydrazyl) free radical and ninhydrin method, respectively.The results of growth curve showed that the growth rate of L. plantarum D28 was faster than E. faecium B21 under the same culture condition, and the stationary growth phase of L. plantarum D28 and E. faecium B21 occurred at 18 h and 16 h, respectively. The growth rate of the two strains was affected by different initial pH; pH ranges of 5.5-7.0 and 6.0-7.0 were most favorite initial pH for L. plantarum D28 and E. faecium B21, respectively. Moreover, L. plantarum D28 had a good tolerance against NaCl (5%) and bile salt (0.15%) in vitro, and E. faecium B21 had a better tolerance against NaCl (8%) and bile salt (0.45%). Time- dependent behavior was found in the bacterial survival amount under the artificial gastric juice (pH 2.0) and artificial intestinal juice (pH 8.0) conditions. After treatment with artificial gastric juice (pH 2.0) for 180 min, the survival rate of L. plantarum D28 was higher than E. faecium B21, remaining 41.33 lg (CFU/mL) and 8.33 lg (CFU/mL), respectively. Moreover, similar result was found with treatment of artificial intestinal juice (pH 8.0) for 240 min, 36.33 lg (CFU/mL) and 18.67 lg (CFU/ mL) for L. plantarum D28 and E. faecium B21, respectively. In addition, the two strains had certain antioxidant activity in vitro, and L. plantarum D28 had a higher DPPH free radical scavenging activity (34.86%) than that of E. faecium B21 (25.32%). Besides, both of the two stains had bile salt hydrolase (BSH) activity, and E. faecium B21 (0.415 U/mg) had a higher BSH activity than that of L. plantarum D28 (0.114 U/mg).In conclusion, the growth rate of the two strains is affected by different initial pH, and L. plantarum D28 has a higher growth rate than E. faecium B21. L. plantarum D28 and E. faecium B21 both have tolerance to acid, bile salt, and NaCl, and are able to survive under the conditions of artificial gastric juice and artificial intestine juice. Therefore, both L. plantarum D28 and E. faecium B21 can be used as candidate for probiotic strains and application for lowering cholesterol research, and L. plantarum D28 can especially be applied to antioxidant-related research.